A novel home automation distributed server management system using Internet of Things. Issue 1 (31st December 2022) - Manojkumar, P.; Suresh, M.; Ayub Ahmed, Alim Al; Panchal, Hitesh; Rajan, Christopher Asir; Dheepanchakkravarthy, A.; Geetha, A.; Gunapriya, B.; Mann, Suman; Sadasivuni, Kishor Kumar
Abstract : In this work, the Home Automation System (HAS) with low cost and wireless remote control module is designed. Internet of Things (IoT) is also implemented along with HAS for monitoring and controlling the home appliances via World Wide Web. Raspberry pi and ESP8266 module use 3.3V TTL logic and the module can be configured to connect with the existing home internet Wi-Fi router through AT commands. So, it can be connected automatically to the configured Wi-Fi network without any initialisations. For switching the load, relays are used for high load current switching capability. Raspberry pi GPIOs can deliver only 20mA of current at 3.3V. The Hall Effect sensor is connected to each load supply line to monitor the current drain by the load. Based on the current drain, the status and power consumption reduces 30% of the load.